Véhicules connectés: Contributions à la communication véhicule-réseau mobile et la localisation coopérative - Chekkkouri, Ahmed Salim (ProQuest Dissertations & Theses, 2015)
Connected Vehicles are a new intelligent transportation paradigm that uses wireless communications to improve traffic safety and efficiency. It has received a great deal of attention in recent years, across many communities. While the DSRC is widely recognized as the de facto standard for V2V, other wireless technologies are required for large-scale deployment of V2I communications. Thanks to its high data rates and large scale deployment, the LTE-A enhanced by small cells densification, is positioned as one of the major candidate technologies for V2I communications. However, using LTE-A small cells for V2I communications is challenging due to their small coverage which lead to frequent handoffs and more signaling overhead. Thanks to recent advances in LTE-A Releases-10/11/12, the 4G LTE-Advanced (LTE-A) mobile network appears as one of the major candidate technologies for V2I communications. In fact, the LTE-A promises to deliver reduced connection setup time and lower latency (10ms) and higher data rates (up to 1Gbps) by using new physical layer technologies and new network elements and functions such as, network densification using Small Cells (SCs), Dual Connectivity (DC), Relaying functionality, Carrier Aggregation (CA), Device to Device (D2D) communication, etc.; developments that pave the way to 5G in the Horizon 2020, with the promise of an even higher data rates (more than 10 Gbps) and even much lower latency (1ms), which reinforces the trend for future integration between VANET and mobile networks for V2I communications. Although the macrocell will remain the major Radio Access Network (RAN) element for wide-area coverage and high-mobility users, it is no longer sufficient to meet user's demand in many high-density areas. Indeed, due to the proliferation of mobile devices and applications, mobile data demand continues to grow exponentially. Small cells, which include microcells, picocells, and femtocells, are widely recognized as a key solution for enhancing RAN capacity and coverage. They are increasingly used by mobile operators, in the so-called Heterogeneous Network (HetNet), to offload traffic from their macrocells. A HetNet is typically composed of several layers (macrocells, small cells), and in some cases different access technologies (e.g., LTE-A, UMTS, WiFi). SCs densification involves deploying more small coverage base stations in high demand areas to bring higher spectral efficiency per coverage area. Nevertheless, the SCs deployment faces a number of problems relevant to mobility handling that have to be addressed. More specifically, the use of SCs with limited coverage causes frequent handovers that lead to high signaling overhead toward the core network. In addition, since the small cells are generally connected to the EPC via a network Internet connection, this one becomes the bottleneck for handovers and data forwarding, hence the importance of completing a maximum of handover locally. This thesis therefore aims to propose solutions for VANETs and mobile networks integration. The main contributions of this thesis are summarized as follows: The first contribution concerns the proposed cooperative localization algorithms, based on a set-membership approach which improves the location accuracy. The first algorithm called (CLES) is a generic algorithm for cooperative localization based on a set-membership approach. The second algorithm called (CLEF) is an application of CLES algorithm to fingerprinting localization. In addition, we characterize their accuracy by evaluating the reduction of the maximum diameter and the area of the polygon depending on various parameters such as the number of polygons, the geometric configuration, the nearest node in relation to the boundary of the polygon, and the uncertainty of distance measurements. The second contribution concerns the selection of mobile gateways to effectively connect vehicles to small cells of the mobile network. In fact, while each vehicle may directly uses its LTE-A interface for V2I communications, we argue that by selecting a limited number of GWs, we can effectively reduce the mobility signaling overhead. Hence, we propose a new network-based mobile gateway selection scheme with one-hop clustering to efficiently relay the traffic from neighbouring vehicles toward the serving SC. The selection problem is formulated as a multi-objective binary linear programming problem. Using linear programming solver, we show that, for realistic number of vehicles per small cell and GW connectivity degree, the execution time is relatively short. As a third contribution of this thesis, we focus on challenges relevant to mobility for VANETs using LTE-A network. Specifically, a novel architecture that integrates VANET and 4G LTE-A Heterogeneous Network for enhanced mobility in LTE-A small cells is introduced. First, we propose a new network-based mobile gateway selection scheme with one-hop clustering to efficiently relay traffic from neighbouring vehicles toward the serving SC. The problem is formulated as a multi-objective binary programming problem. Then, for seamless mobility of connected vehicles, we propose a local k-hops anchor-based mobility scheme with three procedures, namely intra-domain, k-hops inter-domain and inter-domain procedures. Numerical results show the effectiveness of the proposed mobility schemes for reducing the generated signaling load towards the core network.